Final report. Nematode survey - Riedel, RM (International Center for Tropical Agriculture, 1978)
A survey was conducted on 205 soil samples collected from 12 sites in Colombia of different crops, including beans on which the research was mainly focussed (132 soil samples from 10 sites), in order to characterize problems of nematodes in the different regions, make comparisons, and suggest research priorities and control measures. Results indicate that Meloidogyne spp. (M. hapla at higher elevations, M. incognita and M. arenaria at warmer temp., and M. javanica at very warm temp.) is the most limiting nematode for bean production and the most widespread. It is followed in importance by Pratylenchus spp. (P. penetrans, P. crenatus, P. vulnus, P. zeae, and P. brachyurus). In more restricted areas species of Helicotylenchus, Ziphinema, Longidorus, Cacopaurus, Scutellonema, and Rotylenchus were identified. Crop losses caused by Meloidogyne can be evaluated in field trials with nematocides like oxamyl (2-4 lb a.i./ac at planting and 1 lb a.i./ac after 3 wk. as foliar spray). Sources of var. resistance to M. incognita and M. javanica have been identified. Soil temp. alters plant resistance; therefore, this factor must be taken into account by breeding programs. Weed control with herbicides should be investigated as a means of controlling nematodes. Research programs on the control of Meloidogyne should be appicable to Pratylenchus. In the case of the rest of the genera mentioned, it is important to determine the economic damage they can cause. The results of another survey on the collection and identification of nematodes in soil and bean root samples from 8 sites in Colombia are included. (CIAT)